Informed Trading When Information Becomes Stale - Bernhardt, Dan; Miao, Jianjun (Journal of Finance, 2004)
ABSTRACT This paper characterizes informed trade when speculators can acquire distinct signals of varying quality about an asset's value at different dates. The most reasonable characterization of private information about stocks is that while information is long‐lived, new information will arrive over time, information that may be acquired by others. Hence, while a speculator may know more than others at a moment, in the future, his information will become stale, but not valueless. In an environment that allows for arbitrary correlations among signals, we characterize equilibrium outcomes including trading, prices, and profits. We provide explicit numerical characterizations for different informational environments.